Microclimates of Urban Reproduction: The Limits of Automating Environmental Control. Issue 3 (6th August 2019) - Lockhart, Andy; Marvin, Simon
Abstract: Enclosed, controlled environments, stretching from sites of luxury consumption to urban food production, are proliferating in cities around the world, utilising increasingly advanced techniques for (re)creating and optimising microclimatic conditions for different purposes. However, the role of automated control systems—to filter, reprocess and reassemble atmospheric and metabolic flows with growing precision—remains under‐researched. In this article, we explore the phenomenon of automated environmental control at three sites in the UK city of Sheffield: a botanical glasshouse, a luxury hotel and a university plant growth research lab. In doing so, we first show how controlled environments are constituted through specific relations between the inside and outside, which are embedded in inherently political urban contexts and processes. Second, we identify the technical and ecological tensions and limits of indoor environmental control at each site which limit the scope of automation, and the considerable amount of hidden labour and energy required to maintain and restabilise desired conditions. Drawing on these more established examples of ecological interiorisation in a key moment of transition, we raise urgent questions for critical urban and environmental geographers about the possible futures of controlled environments, their practical or selective scalability, and who and what will be left "outside", when they are emerging as a strategic form of urban adaptation and immunisation in the face of converging ecological pressures.